ಚಾರಿತ್ರಿಕ ದಾಖಲೆಗಳು - (:unkn) unknown (Kannada Sahitya Parishattu, 1999)
This book is an collection of Historical Documents of Mysore Dynasty and other Kings
Charitrika Dakhalegalu
Keywords: Kannada; ಚಾರಿತ್ರಿಕ ದಾಖಲೆಗಳು; Charitrika Dakhalegalu; History; Kannada; Kannada